If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10x + 1 + -7 = -17x + 7 Reorder the terms: 1 + -7 + -10x = -17x + 7 Combine like terms: 1 + -7 = -6 -6 + -10x = -17x + 7 Reorder the terms: -6 + -10x = 7 + -17x Solving -6 + -10x = 7 + -17x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '17x' to each side of the equation. -6 + -10x + 17x = 7 + -17x + 17x Combine like terms: -10x + 17x = 7x -6 + 7x = 7 + -17x + 17x Combine like terms: -17x + 17x = 0 -6 + 7x = 7 + 0 -6 + 7x = 7 Add '6' to each side of the equation. -6 + 6 + 7x = 7 + 6 Combine like terms: -6 + 6 = 0 0 + 7x = 7 + 6 7x = 7 + 6 Combine like terms: 7 + 6 = 13 7x = 13 Divide each side by '7'. x = 1.857142857 Simplifying x = 1.857142857
| (4y-5)(6+y)=0 | | -3=27a-3(2a-3) | | ln(2x+11)=0 | | 9x-1+1x=3 | | 2t-4+4t=6t-4 | | 6x^2+y^2=1 | | 70n^2=30+8n | | -5(1-5x)+5(-8x-2)=-4x+8x | | 5(x+6)=14x-4x+10 | | 20x^4y+25x^2=0 | | 8x^3y^5-12x^2y^8+36x^4y^10=0 | | X^4=54 | | 14x-3=14-3x | | -(-1+10y)=-20-31y | | l(20-l)=36 | | -4.9*x^2+9.8x+0=3.675 | | Y=18x^2+81 | | 14x+2x=12x+6+10x | | 100x^2+25=0 | | 14x+3x+10x=6 | | log[4](2x-3)=3 | | 5r-29=-23+3r | | 3(x+4y)+7y=6 | | 289.80=9(0.08m+22.80+0.10(22.80)) | | 14x+2x=3x+6+10x | | Y^2-32y+175=0 | | 2(3x-2)+4=30-3x | | 2x+7-3x=25+2x | | 42n-7=13 | | log(2x+3)=1.5 | | 24x^2+112=-184x | | 9*(x-5.3)=8.1 |